2005
DOI: 10.1038/sj.onc.1208566
|View full text |Cite
|
Sign up to set email alerts
|

CpG island promoter hypermethylation of a novel Ras-effector gene RASSF2A is an early event in colon carcinogenesis and correlates inversely with K-ras mutations

Abstract: We report in silico identification and characterisation of a novel member of the ras association domain family 1 (RASSF1)/NORE1 family, namely, RASSF2, located at chromosomal region 20p13. It has three isoforms, all contain a ras association domain in the C-terminus. The longest isoform RASSF2A contains a 5 0 CpG island. RASSF2A was cloned from a brain cDNA library and directly sequenced, confirming the genomic gene structure. In previous reports, we and others have demonstrated that RASSF1A is epigenetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
121
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(141 citation statements)
references
References 27 publications
17
121
2
1
Order By: Relevance
“…RASSF2A expression is frequently lost or downregulated due to tumour-specific promoter CpG island hypermethylation in up to 70% of colorectal carcinomas (CRCs). This is one of the earliest events in CRCs detectable in adenoma polyps (Akino et al, 2005;Hesson et al, 2005). In fact, inactivation of RASSF2A is much earlier and more frequent in CRCs than inactivation of RASSF1A, which occurs at around 15-45% (Akino et al, 2005;Hesson et al, 2005).…”
Section: Rassf1mentioning
confidence: 98%
See 2 more Smart Citations
“…RASSF2A expression is frequently lost or downregulated due to tumour-specific promoter CpG island hypermethylation in up to 70% of colorectal carcinomas (CRCs). This is one of the earliest events in CRCs detectable in adenoma polyps (Akino et al, 2005;Hesson et al, 2005). In fact, inactivation of RASSF2A is much earlier and more frequent in CRCs than inactivation of RASSF1A, which occurs at around 15-45% (Akino et al, 2005;Hesson et al, 2005).…”
Section: Rassf1mentioning
confidence: 98%
“…This is one of the earliest events in CRCs detectable in adenoma polyps (Akino et al, 2005;Hesson et al, 2005). In fact, inactivation of RASSF2A is much earlier and more frequent in CRCs than inactivation of RASSF1A, which occurs at around 15-45% (Akino et al, 2005;Hesson et al, 2005). It has recently been shown that methylation in a subset of genes in CRCs and matching faecal tissue may form a basis for early detection (Muller et al, 2004).…”
Section: Rassf1mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Sakamoto et al (2004) have shown that the early flat-type colorectal tumours exhibited a much higher frequency of RASSF1 methylation (81.3%). The frequency of RASSF2 methylation in CRC was reported to be 42 -73% (Akino et al, 2005;Hesson et al, 2005;Park et al, 2006).…”
mentioning
confidence: 99%
“…In addition, clinicopathological features of colorectal tumours that carry the methylation of either RASSF1 or RASSF2 are still largely unknown in adenomas as well as in cancers. Moreover, the association between K-ras/BRAF mutations and RASSF methylation, particularly whether or not they work synergistically or are mutually exclusive, is controversial in CRCs (Akino et al, 2005;Hesson et al, 2005;Park et al, 2006), and has not been sufficiently investigated in adenomas.…”
mentioning
confidence: 99%